2016
DOI: 10.1080/09540121.2016.1263723
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a 16-week aerobic exercise programme on cognitive function in people living with HIV

Abstract: High levels of cardiovascular fitness and physical activity are associated with higher levels of cognitive function in people with HIV, thus, they may reduce the risk of developing HIV-associated neurocognitive disorder (HAND). This study aimed to investigate the effects of a 16-week aerobic exercise intervention on cognitive function in people with HIV. Eleven participants living with HIV were recruited into the study. Participants were randomised into either an exercise group (n = 5), that completed a 16-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(106 citation statements)
references
References 25 publications
2
104
0
Order By: Relevance
“…The initial search yielded 795 potential citations of which seven publications were considered eligible to be included in the review. Using the primary outcome measured in each study, mental health included seven publications [23,[34][35][36][37][38] while physical activity included only one publication [34]. However, no study reported the effect of exercise intervention on social participation.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial search yielded 795 potential citations of which seven publications were considered eligible to be included in the review. Using the primary outcome measured in each study, mental health included seven publications [23,[34][35][36][37][38] while physical activity included only one publication [34]. However, no study reported the effect of exercise intervention on social participation.…”
Section: Search Resultsmentioning
confidence: 99%
“…Reasons for exclusion of studies following full-text screening included: studies had a control group that was exercising (n= 1), pre-test -post-test study design with no control group (n =1), Non-Randomized control trials (n=3), studies with missing data (n=2), studies with a non-human population (n=1), studies that did not have outcome measure of interest (n=1) ( Figure 2). [34]. For aerobic and resistance exercises: Jaggers, Hand [36] has a control group that engaged in the sedentary activity; while a study Fillipas, Oldmeadow [37] had Unsupervised walking programme as control and another study Dianatinasab, Fararouei [23] has a "behavioural disease counselling and treatment" control group.…”
Section: Reasons For Exclusionmentioning
confidence: 99%
See 3 more Smart Citations